Plants changed the response of bacterial community to the nitrogen and phosphorus addition ratio - Zhang, Zehao; Sun, Jingkuan; Li, Tian; Shao, Pengshuai; Ma, Jinzhao; Dong, Kaikai (Frontiers in Plant Science, 2023)
Human activities have increased the nitrogen (N) and phosphorus (P)supply ratio of the natural ecosystem, which affects the growth of plants and the circulation of soil nutrients. However, the effect of the N and P supply ratio and the effect of plant on the soil microbial community are still unclear. In this study, 16s rRNA sequencing was used to characterize the response of bacterial communities in Phragmites communis (P.communis) rhizosphere and non-rhizosphere soil to N and P addition ratio. The results showed that the α-diversity of the P.communis rhizosphere soil bacterial community increased with increasing N and P addition ratio, which was caused by the increased salt and microbially available C content by the N and P ratio. N and P addition ratio decreased the pH of non-rhizosphere soil, which consequently decreased the α-diversity of the bacterial community. With increasing N and P addition ratio, the relative abundance of Proteobacteria and Bacteroidetes increased, while that of Actinobacteria and Acidobacteria decreased, which reflected the trophic strategy of the bacterial community. The bacterial community composition of the non-rhizosphere soil was significantly affected by salt, pH and total carbon (TC) content. Salt limited the relative abundance of Actinobacteria, and increased the relative abundance of Bacteroidetes. The symbiotic network of the rhizosphere soil bacterial community had lower robustness. This is attributed to the greater selective effect of plants on the bacterial community influenced by nutrient addition. Plants played a regulatory role in the process of N and P addition affecting the bacterial community, and nutrient uptake by the root system reduced the negative impact of N and P addition on the bacterial community. The variations in the rhizosphere soil bacterial community were mainly caused by the response of the plant to the N and P addition ratio.